Environmental determinants for participation among stroke survivors in Africa, a scoping review - Assefa, Yohannes Awoke; Demeke, Zelalem Dessalegn; Wolde, Sara; Guadie, Yisak Girma (Frontiers in Rehabilitation Sciences, 2023)
Purpose In this review, we aimed to determine the environmental factors that are influencing the participation of stroke survivors in Africa. Methods Four electronic databases were systematically searched from inception to August 2021, and identified articles were screened by the two authors of this review based on predetermined criteria. No date restrictions were imposed, and we included any type of paper, including gray literature. We followed the scoping review framework by Arksey and O'Malley, which was later revised by Levac et al. The whole finding is reported using the preferred reporting items for systematic reviews and meta-analyses extension for scoping reviews (PRISMA-ScR). Results A total of 584 articles were generated by the systematic search, and one article was added manually. After eliminating the duplicates, the titles and abstracts of 498 articles were screened. From the screening, 51 articles were selected for full article review, of which 13 met the criteria to be included. In total, 13 articles were reviewed and analyzed based on the international classification of functioning, disability, and health (ICF) framework of the environmental determinants. Products and technology; natural environment and human-made changes to environment; and services, systems, and policies were found to be barriers for stroke survivors to participate in their community. Conversely, stroke survivors are getting good support from their immediate family and health professionals. Conclusion This scoping review sought to identify the environmental barriers and the facilitators that are determining the participation of stroke survivors in Africa. The results of this study can serve as a valuable resource for policymakers, urban planners, health professionals, and other stakeholders involved in disability and rehabilitation. Nonetheless, additional research is necessary to validate the identified facilitators and barriers.